4CPS-212 Specialist pharmacist-led multidisciplinary care pathway for optimising lipid therapy – six months interim analysis. Issue 1 (23rd March 2023) - Hamedi, N; Ali, S; Robson, J; Patel, R; Albert, H; Khan, I; Kearney, M; Krishek, B; Fhadil, S; Wright, P; Antoniou, S
Abstract : Background and Importance: Cardiovascular disease (CVD) is a leading cause of mortality worldwide and accounts for approximately 27% of all deaths in United Kingdom. The relationship of hypercholesterolemia to CVD is well established and understood in terms of atherogenesis. Reduction of atherogenic lipoproteins, in particular, low-density lipoprotein with lipid modification treatments has been shown to reduce the risk of CVD events and mortality. Aim and Objectives: Design, test and develop an integrated care pathway that utilises specialist cardiovascular pharmacists working with primary care teams. This involves optimising secondary prevention with lipid modification therapy in people with established CVD across 42 General Practitioner practices over one-year pilot programme . Material and Methods: Specialist cardiovascular pharmacists were commissioned to work with primary care clinicians to identify, review and optimise secondary prevention in high-risk patients not receiving lipid modification therapy. Eligible patients' clinical notes were reviewed to confirm CVD diagnosis, history of treatment, blood test results and CVD risk factors. Complex cases were reviewed by a virtual lipid specialist multidisciplinary team to agree a treatment plan. Patients were contacted for a virtual consultation to discuss and initiate tailored lipid modification therapy. Results: A preliminary review of practices CVD list showed 20% (2200/11233) of patients had a CVD diagnosis and were not receiving lipid modification therapy. A six-month interim analysis of 1100 out of the 2200 clinical reviews conducted by specialist pharmacists, identified that 60% (660/1100) were eligible for statin therapy with only 4% (44/1100) of patients having a true statin intolerance. The remaining 36% (396/1100) were not for lipid modification therapy. Of these patients: 6% (66/1100) declined treatment, 9% (96/1100) were palliative or the risk of treatment outweighed the benefits, 8% (90/1100) had non-atherosclerotic CVD, 9% (100/1100) had incorrect CVD diagnosis and the remaining 4% (44/1100) were no longer part of the practice list. Conclusion and Relevance: An integrated care pathway using specialist cardiovascular pharmacists supporting a multidisciplinary workforce within primary care has shown a significant improvement in lipid modification therapy prescribing to reduce the risk of myocardial infarction (MI) and stroke. Extrapolating these results nationally would avert 17, 000 MIs and 5, 000 strokes over a 5-year period. References and/or Acknowledgements: Conflict of Interest: No conflict of interest